Top Human Resources Managers Views on Trade Union Action in Brazilian Corporations - Antonio Carvalho Neto; Wilson Aparecido Costa de Amorim; André Luiz Fischer (BAR: Brazilian Administration Review, 2016)
This article presents the perception of human resource (HR) top managers at strategic level in Brazilian corporations regarding labor union activity. It is a quantitative study about the perception of 354 experienced HR top managers on the unionization of employees, influence of the union on the organization, recognition of the union for labor negotiations and the existence of an advisory committee (workers’ council) within organizations. The theoretical approach addresses both the fields of study on HR and Industrial Relations (IR). The research shows low unionization and management perceptions that unions have little influence on organizations. On the other hand, the HR managers recognize the union influence for collective bargaining purposes and for defining general terms of employment. These contradictions are related to the fact that collective bargaining is mandatory in Brazilian legislation. In general terms of employment, Brazilian legislation is too rigid, prescriptive and detailed. This strong state of regulation reserves to the union an automatic participation in the negotiation process with employers, although this trade union action is somehow inefficient. In this scenario, the perception of HR managers of a relative union influence, although inefficient, is an expected consequence.